Association between socioeconomic status and dental caries among Chinese preschool children: a cross-sectional national study. Issue 5 (21st May 2021) - Zhang, Tingting; Hong, Jialan; Yu, Xueting; Liu, Qiulin; Li, Andi; Wu, Zhijing; Zeng, Xiaojuan
Abstract : Objectives: Socioeconomic inequalities in oral health are often neglected in oral health promotion. This cross-sectional study assessed the association between dental caries and socioeconomic status (SES) among preschool children in China. Design: Cross-sectional study. Setting: Data from the Fourth National Oral Health Survey of China (2015), comprising of 40 360 children aged 3–5 years was used. Methods: Dental caries indicators including prevalence of dental caries, dental pain experience and number of decayed, missing and filling teeth (dmft). SES indicators included parental education and household income. The associations between SES and dental caries were analysed by using negative binomial regression or Poisson regression models according to data distribution. Relative and absolute inequalities in dental caries were quantified by using the Relative Index of Inequality (RII) and Slope Index of Inequality (SII), respectively. Results: There were significant associations between SES and prevalence of dental caries and dmft (p<0.001). Children from lower educated (RII 1.36, 95% CI 1.3 to 1.43; SII 0.97, 95% CI 0.81 to 1.13) and lower household income (RII 1.17, 95% CI 1.11 to 1.24; SII 0.55, 95% CI 0.35 to 0.75) families had higher dmft than those from well-educated and most affluent families. Relative and absolute inequalities in dental caries were larger in urban areas by household income, and in rural areas by parental education. Conclusions: Association between dental caries and SES was demonstrated and socioeconomic inequalities in dental caries existed among Chinese preschool children.